NUMERICAL OPTIMIZATION OF THE EFFECT OF THE ASPECT RATIO ON THE DYNAMIC PERFORMANCE OF PLATES - ASKER, HAVAL (Journal of Duhok University, 2023)
This paper intends to study, investigate and optimize the effect of aspect ratio such as width and height on the dynamic behavior of a plate in terms of frequency and mode shapes.The research involves simulating and building plate models using ANSYS software. Modal analysis is adopted to predict the dynamic behavior of the plate. MATLAB code is developed to estimate the natural frequency values mathematically. Numerical results are compared with mathematically calculated frequency values. A total of 25 ANSYS models are built. The study has investigated up to eight dynamic modes shapes. The effects of the aspect ratios are presented in this article. Increasing the width can slightly increase the natural frequency values however increasing the thickness can significantly increase the values of the natural frequency. The range of the width values was from 40, 45, 50, 55, and 60 mm. The range of thickness values was from 10, 15, 20, 25, and 30 mm. This effect was seen to take place more in flexural (bending) modes. Flexural, Lateral, torsional, and buckling mode types were observed during the modal analysis. The rank of these modes for each model was dependent on the width and height of the plate.